FIGURATIVE LANGUAGE USED IN PUBLIC INFORMATION NOTICES IN MALANG. - Akhirita, Inggit Nindya (Jurnal Ilmiah Mahasiswa FIB, 2013)
English language and Literature Department, University of Brawijaya.Public information notice is one application of delivering messages using written language. In Malang there are a lot of public information notices found in public places especially in crowded area such as Pasar Besar area and campus area. In the application, some public information notices use figurative language to gain certain effect for the readers. Figurative language is the utterance or expression used to express things in unusual way. Using Reaske (1966) definition of figurative language and Yule (1996) theory of context, this study is aimed to identify (1) the types of figurative language found in public infomation notice in Malang (2) the meaning of figrative language used in public information notice.This study uses qualitative approach in relation of the document analysis. The document analysis is intended to provide clear description about the text in the public information notice.This study finds that (1) figurative languages used in the public information notices in Pasar Besar area and campus area in Malang are sarcasm, metaphor, irony, synecdoche, hyperbole, and personification. Satire is mostly used in Pasar Besar area while personification is dominant in the campus area, (2) The meaning of the utterance in public information notices depends on the situational context and background knowledge of the readers.The writer suggests the next researchers conduct similar research about figurative language by using different point of view or objects. Many phenomena are found in the application of language in daily life. Moreover, the next researhers are able to find other theories concerning the idea of figurative language.